EDUKASI DAN IMPLEMENTASI FITUR DETEKSI RISIKO PENYAKIT DI APLIKASI SATUSEHAT DI PUSKESMAS KESUNEAN KOTA CIREBON - Khasanah, Lina; Fitria Dewi Rahmawati; Yanto Haryanto (Indonesian Journal of Health Information Management Services, 2025)
Advances in digital technology in the health sector have created significant opportunities for health workers to enhance their ability to detect non-communicable diseases (NCDs) at an early stage. The use of the risk detection feature in the SatuSehat application at the primary service level is still limited because some officers do not understand how to use it and its benefits in promotive and preventive activities. This community service program aims to strengthen the knowledge and skills of Puskesmas staff in using the SatuSehat application as a tool for early detection of NCDs. The method employed was training with a participatory educational approach, involving the presentation of materials, live demonstrations, discussions, and evaluations through pre- and post-tests. The activity was conducted at the Kesunean Health Center in Cirebon City and involved 25 health workers. The results showed an improvement in participants’ knowledge, with the average pre-test score increasing from 79 to 90 in the post-test. Several participants were introduced to the early detection feature for the first time during the training and expressed strong interest in applying it. The training contributed to improving digital literacy among health workers and strengthening NCD prevention efforts at the primary care level.